Studying pharmacokinetic parameters of engineered Bradykinin drugs (SFBK and BKSF) in mice. - Li, GuoAn. (2013)
The aim of this study was to examine the pharmacokinetic parameters of engineered bradykinin drugs (SFBK and BKSF) using oral delivery method in mice. In the previous study, we have shown that the SFBK drug have pH, pepsin and trypsin stability. BKSF drug have pH and pepsin stability but lack of trypsin stability. A single administration for both SFBK and BKSF drugs (100 mg/kg) were orally delivered into the stomach of the mice and the blood was collected for five different time intervals; 0, 2, 3, 4 and 5 hours. A SFBK and BKSF standard calibration curve was obtained using the standard addition method with a set of known concentration; 100, 50, 25, 12.5, 6.25 and 3.125 μM. The correspondent equation for SFBK and BKSF standard calibration curve was y = 344848x + 179776 and y = 495119x + 2e+06 respectively. Blood samples collected from the mice were analyzed using the RP-HPLC and the results obtained from the chromatographs were compared to the standard addition calibration curve. 7.3494 μM of SFBK drug concentration was obtained from the blood samples at 2 hour when 30 mg/kg of SFBK drug dosage was used. The SFBK drug dosage was then increased to 100 mg/kg and the highest SFBK concentration of 30.292 μM was obtained at 3 hour which was approximately 4 times higher than the initial SFBK drug dosage. When 100 mg/kg of BKSF drug dosage was used, 10.842 μM of BKSF drug concentration was observed at 2 hour, which was approximately 3 times lower than the SFBK drug concentration. This effect may be explained by the lack of trypsin inhibitor in BKSF drug, which may leads to an increase in tryptic degradation in the gastrointestinal tract.